Case Report: Infant with vaccine-associated paralytic poliomyelitis unveils global disparities in care for inborn errors of immunity - Chan, Chee Mun; Fong, Elisabeth Sue Shuen; Yeo, Daryl Yuan Chong; Ang, Elizabeth Y.; Liu, Isabella Ming Zhen; Ong, Hian Tat; Chan, Si Min; Chin, Hui-Lin; Yeap, Frances Shi Hui; Kee, Chee Kwang; Tan, Teresa Shu Zhen; Ng, Nicholas Beng Hui; et al. (Frontiers in Immunology, 2026)
Severe combined immunodeficiency (SCID) is a life-threatening inborn error of immunity (IEI) that is potentially curable when diagnosed early but is associated with high morbidity and mortality when recognition is delayed. In settings without universal newborn screening (NBS), and where vaccination programs rely heavily on live vaccines, affected infants are at risk of preventable complications.We report an Indonesian girl, the first child of non-consanguineous parents, who at the age of three months, developed a generalized maculopapular rash, followed by febrile encephalopathy with acute flaccid paralysis and hepatomegaly at four months of age. Investigations revealed pan-hypogammaglobulinemia (IgG <1.09 g/L, IgA <0.05 g/L, IgM 0.06 g/L) and marked eosinophilia (7554 cells/uL). On transfer to Singapore, detailed immunophenotyping revealed T cell lymphocytopenia with the vast majority being 99.3% CD45RO+ on CD3+CD4+ cells, and absent B cells. The diagnosis of SCID with Omenn syndrome was made, with genetic analysis revealing compound heterozygosity for pathogenic RAG1 variants. As the child received oral polio vaccine (OPV) at day 8 of life, vaccine-associated paralytic poliomyelitis (VAPP) was suspected, which was confirmed with positive enterovirus PCR in the cerebral spinal fluid; Sabin-like poliovirus serotype 1 was isolated from stool. Hematopoietic stem cell transplantation (HSCT) was discussed but the family opted for supportive palliative care. The child died of a febrile illness at 8 months of age.Although IEI was initially suspected, the use of limited flow cytometric diagnostic evaluation delayed the definitive diagnosis in the child. The lack of NBS for SCID, together with the continued usage of OPV in the routine childhood vaccination program in most lower to middle income countries is the perfect storm for VAPP in children born with IEIs in these settings. This case highlights that 1) there is an urgent need to strengthen diagnostic capabilities in resource-limited settings, 2) the transition from OPV to inactivated polio vaccine (IPV) is a public health priority, and 3) there are significant barriers to the implementation of SCID NBS in Southeast Asia. Addressing these systemic gaps is critical to improve survival outcomes for children with severe but treatable IEIs.